PENGARUH KOMPENSASI FINANSIAL DAN NON FINANSIAL TERHADAP KINERJA KARYAWAN TERHADAP PT. PLN (Persero) UP3 MAKASSAR UTARA - Nurul Jirana Rahmadhani Syam; Agung Widhi Kurniawan; Nurman; Romansyah Sahabuddin; Uhud Darmawan Natsir (Lafadz Jaya Publisher, 2023)
The objective of this study is to know the effects of financial and non-financial compensation both partially and simultaneously. The sample was used by 56 employees in PT. PLN (Persero) UP3 North Makassar has been selected based on the criteria that have been determined first. Data collection techniques are done with questionnaires and library studies. Data analysis techniques consist of validity tests, rehabilitation tests, classical assumption tests based on normality tests, multicolinearity tests and heteroskedasty tests, double linear analysis tests, hypothesis tests, determinant coefficient tests. The findings in this variable showed that partially the variable X1 is, financial compensation is positive and has a significant impact on employee performance, while the X2 is, non-financial compensation has a negative and significant influence on variable Y, the employee’s performance. Based on the results of this analysis, it can be seen that partially variable financial compensation influencing the performance of employees (H1) was received. It is known that partially variable non-financial compensation has a negative but significant impact. H2 is rejected. From the results of this analysis it can also be seen that simultaneously financial compensation and non-financial compensation have a significant impact on employee performance. H3 is accepted